Patterns of transfusion burden in an unselected population of patients with myelodysplastic syndromes: A population‐based study. Issue 10 (3rd September 2021) - Rozema, Johanne; van Roon, Eric N.; Kibbelaar, Robby E.; Veeger, Nic J. G. M.; Slim, Christiaan L.; de Wit, Harry; Hoogendoorn, Mels; ,
Abstract: Background: Ineffective hematopoiesis in patients with myelodysplastic syndromes (MDS) often results in transfusion dependence. The burden of frequent transfusions in the real‐world MDS population is largely unknown. Study design and methods: An observational, retrospective, population‐based study, using the HemoBase registry, was performed including all patients diagnosed with MDS between 2005 and 2017 in Friesland, a province in the Netherlands with approximately 650, 000 inhabitants. Detailed clinical information was collected from the electronic health records. Transfusion burden was classified according to the International Working Group 2018 criteria: not transfusion dependent, low (LTB), or high transfusion burden (HTB). Univariate and multivariable regression analyses were performed. Results: Of 292 patients, 136 (46.6%) had a HTB of ≥8 units/16 weeks and 17 (5.8%) had a LTB of 3–7 units/16 weeks. This was present in all types of MDS patients, but patients aged 75–84 years (odds ratio [OR] 4.02, 95% confidence interval [CI]: 1.84–8.82), high‐risk MDS patients (OR 2.88, 95% CI: 1.08–7.68) and MDS‐EB‐2 patients (OR 7.07, 95% CI: 2.17–22.90) were particularly at risk for a HTB. Discussion: This study provides a reliable estimate of the transfusion burden in real‐world MDS patients, with almost half of the patients having a HTB. A HTB was observed in all MDS subtypes and both low‐ and high‐risk MDS. Therefore, we conclude that the entire MDS population might benefit from novel agents that reduce the transfusion need and that might have beneficial effects on patient outcomes and healthcare utilization outcomes.